La centellografía espleno-renal con BMHP Hg-197 - Rochna Viola, E.M.; Pecorini, Victorio; Kremenchuzky, Silvio; Musso, A.M.; Gotta, Héctor (Comisión Nacional de Energía Atómica (CNEA), 1970)
Fil:Rochna Viola, E.M. Comisión Nacional de Energía Atómica (CNEA). República Argentina